The Development of a Smart Learning Platform to Strengthen Students’ Metacognition - Nur Ardini, Sukma; ., Suwandi; ., Senowarsito; Olanrewaju Adebisi, Rufus (KnE Social Sciences, 2022)
Metacognition Smart Learning (MSLearning) was designed to facilitate teachers and students during the pandemic to conduct a blended learning process where both synchronous and asynchronous learning can be done. The MSLearning platform focuses on metacognition which plays an important role in all learning activities as it helps students to evaluate errors and issues in their problem-solving skills. The objectives of the study were to describe the development of the MSLearning platform and to investigate students’ perceptions of MSLearning. A descriptive qualitative method was employed. A questionnaire about individual perception was distributed to 50 students in 10 junior high schools in Semarang city. The learning process of the MSLearning platform involved 7 phases, from opening to closing the lesson, including synchronous and asynchronous steps. Meanwhile, the findings of the students’ perception questionnaire showed that the MSLearning platform contents are interesting (72%), the platform makes it easy to understand the existing materials (45%), the completeness of the types of learning using MSLearning platform such as presentation, quiz, video, etc (87%), it can be done independently (91%), and the MSLearning platform can help to build new insights and techniques linked to learning objectives (44%). It can be concluded that the MSLearning platform was suitable for seventh-grade junior high school students in Semarang city. The findings othe f the present study will be proceeded by the researchers to revise MSLearning platform in terms of the content and to strengthen students’ metacognition. Keywords: Development, smart learning platform (MSLearning), metacognition